Systematic Literature Review: The Role Of Transfer Pricing Regulations In Reducing Tax - Lestari, Desak Nyoman Lia; Harefa, Tulus; Fuadah, Luk Luk (Jurnal Fokus Manajemen, 2025)
This study aims to examine the role of transfer pricing regulations in reducing tax avoidance practices through a Systematic Literature Review (SLR) approach. The study collects and analyzes 20 scientific articles published between 2018 and 2025, sourced from reputable databases such as Emerald, DOAJ, and ResearchGate. The articles reviewed are publications in either Indonesian or English, fully accessible, and indexed in Scopus, Copernicus, Sinta, or are proceedings from international conferences. The main keyword used in the search process was "transfer pricing." The results of the review show that transfer pricing regulations play a strategic role in preventing tax avoidance practices by multinational companies, particularly through the mechanism of profit shifting to low-tax jurisdictions. Regulations based on the arm’s length principle, supported by instruments such as Advance Pricing Agreements (APA), transfer pricing documentation systems, and the strengthening of criminal law enforcement, have proven effective in limiting opportunities for transfer price manipulation. The effectiveness of their implementation largely depends on factors such as a company’s internal control system, the utilization of technology, the availability of comparable data, and good corporate governance. Additionally, international cooperation through Automatic Exchange of Information (AEoI), Country-by-Country Reporting (CbCR), and the harmonization of cross-border policies has proven crucial in enhancing transparency and monitoring cross-jurisdictional transfer pricing practices. These findings underscore the importance of a comprehensive and collaborative approach to strengthening transfer pricing regulations as a global tax avoidance control instrument.